Impact analysis of agile method based on risk management for developing technology management in (SMEs) Small and Medium- Enterprises - Younus, Ahmed Muayad; Abumandil, Mohanad (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Nowadays, information systems such as the Agile model can adapt to the structures and processes of smart organizations, particularly SMEs. The faster an information technology company adopts risk management-based Agile in a work environment, the higher its performance and energy efficiency. To maximize the value generated by agile decision-makers or managers, SMEs must have the capability and willingness to adopt new risk management-based technology models. Additionally, the study identifies a gap in the use of the Agile Model to influence the success of SME projects in the Middle East region's SMEs (, UAE, KSA, Oman, Egypt, Iraq, and Qatar). The study is aimed at SMEs in the electronics and energy sectors, as well as IT businesses and big data projects, with the goal of encouraging them to adopt an Agile model. This study was characterized positively in numerous ways, including the adoption of technology in the workplace to accommodate abrupt changes in energy management schemes and various government policies promoting energy conservation. Additionally, employee training and adaptability in dealing with programs that can affect the process help accomplish the objectives. Restructuring medium and small businesses to improve their energy management and overall performance.